Scintigraphy in the Evaluation of Osteoarthritis of the Canine Stifle Joint - Innes, J. F.; Barr, A. R. S.; Patteson, M. W.; Dieppe, P. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
The aim of this study was to investigate the role of scintigraphy in the evaluation of osteoarthritis of the canine stifle joint. Forty dogs with osteoarthritis of the stifle joint were examined scintigraphically using 99mTechnetium hydroxymethylene diphosphonate (99mTc-HMDP). Early (perfusion) and late (bone) scans of both stifle joints from each dog were obtained. Preliminary review of scans suggested three grades of early phase isotope retention (0, 1, 2) and two abnormal patterns of late phase retention (“generalised” and “marginal”). The reproducibility of these gradings/groupings was tested using unweighted kappa (ĸ) tests and found to be good (ĸ = 0.58) to excellent (ĸ = 0.93). Of 73 early phase scans, 35 (48%) showed some abnormality as did 61 (85%) of 72 late phase scans. Where both early and late phase scans were available (n = 65), 58 (89%) were considered abnormal. Results of scans were compared to clinical, radiographic and surgical observations. Scintigraphy was associated with clinical and radiographic data (ρ <0.05) but also appears to provide additional information. The marginal pattern was associated with bodyweight (ρ = 0.018), instability (odds ratio [OR] = 8.82), osteophytosis (OR = 18.64) and intra-articular mineralisation (OR = 31.09). Although not reaching statistical significance, the marginal pattern tended to be associated with articular cartilage fibrillation as observed at arthrotomy. The generalised pattern was seen in the absence of instability, effusion and osteophytosis. Scintigraphy appears to be a useful method for staging osteoarthritis of the canine stifle joint, as well as providing a means to study disease mechanisms.Osteoarthritic canine stifle joints were examined scinti-graphically (early and late phase scans), clinically, radio-graphically and visually at surgery. Abnormal scan grades and patterns were defined, and the reproducibility of these gradings/groupings was tested and found to be good to excellent. Scintigraphic findings were associated with other disease measures but it appears that scintigraphy supplies additional information. Scintigraphy provides a useful method with which to investigate osteoarthritis of the canine stifle joint.
Keywords: Osteoarthritis; scintigraphy; stifle; dog